THE INFLUENCE OF TASK-BASED LEARNING APPROACH AND SELF-CONFIDENCE TOWARD STUDENTS’ SPEAKING ABILITY AT SMAN 4 PALEMBANG - Widya Sartika; Tahrun Tahrun; Magdad Hatim (Universitas Galuh, 2022)
This research aims to analyze the influence of task-based learning approach and self-confidence toward students’ speaking ability. The writer distributed pretest, posttest, and questionnaire in collecting the data. In addition, in analyzing the data, the writer used t-test and two-way ANOVA. The findings of this study were (1) There was a significant difference between the speaking ability of the eleventh grade students who had high self confidence taught by using task-based learning approach that of those who were taught by using conventional technique. (2) There was a significant difference between the speaking ability of the eleventh grade students who had low self confidence taught by using task-based learning approach and that of those who were taught by using conventional technique (3) There was a significant difference between of the speaking ability of the eleventh grade students taught by using task-based Learning Approach and that of those who had high and low self confidence (4) There was any significant difference between of the speaking ability of the eleventh grade students taught by using Conventional technique and that of those who had high and low self confidence (5) There were any significant interaction effects of Task-Based Learning Approach and students’ self confidence towards their speaking ability.